Daya Hambat Teh Kombucha terhadap Pertumbuhan Bakteri dan Jamur pada Bahan Pangan Hewani - Ovi Prasetya Winandari; Winda Isti Utami; Marlina Kamelia; Nurhaida Widiani (Gunung Djati Conference Series, 2021)
The use of chemical preservatives in animal food products can cause health problems. So it needs natural preservatives that can be used as an alternative to prevent food product’s damage. Kombucha fermentation produces acetic acid which can inhibit microbial growth so it can used as natural preservatives of food product. The purpose of this study was to determine the ability of kombucha tea to inhibit the growth of bacteria and fungi in animal food products. This research is an experimental study using Completely Randomized Design (CRD) with 4 treatments and 3 replications. The treatments were P1 (kombucha fermentation for 6 days), P2 (kombucha fermentation for 12 days), P3 (kombucha fermentation for 18 days), and P4 (22 days kombucha fermentation). The research data were analyzed using One Way Annova and further tested using Least Significant Different (LSD). The results showed that fermented kombucha tea can inhibit the growth of bacteria and fungi in animal foods. The treatment that shows most strongly inhibited the growth of bacteria and fungi was kombucha tea which was fermented for 22 days.